Three new species of mites of the genus Bakerdania Sasa, 1961 (Acari: Heterostigmata: Neopygmephoridae) from “Cape Martyan” Nature Reserve, Crimea - Khaustov, Alexandr A. (Zootaxa, 2010)
Three new species of mites: Bakerdania latissimosetosa sp. nov., B. undulata sp. nov., and B. martyaniensis sp. nov. collected from soil in “Cape Martyan” Nature Reserve, Crimea, Ukraine are described.